Wave characteristics on the Pacific coast of Costa Rica for energy production - Govaere Vicarioli, Georges (2020)
The iMARES group of the University of Costa Rica has carried out a continuous measurement of the Pacific waves of Costa Rica, from which wave characteristics have been determined and how these can influence the production of electrical energy.